Management of Nasopharyngeal Carcinoma in Elderly Patients - Chan, Wing Lok; Chow, James Chung Hang; Xu, Zhi-yuan; Li, Jishi; Kwong, Wing Tung Gobby; Ng, Wai Tong; Lee, Anne W. M. (Frontiers in Oncology, 2022)
Nasopharyngeal cancer (NPC) is one of the most difficult cancers in the head and neck region due to the complex geometry of the tumour and the surrounding critical organs. High-dose radical radiotherapy with or without concurrent platinum-based chemotherapy is the primary treatment modality. Around 10%–15% of NPC patients have their diagnosis at age after 70. The management of NPC in elderly patients is particularly challenging as they encompass a broad range of patient phenotypes and are often prone to treatment-related toxicities. Chronologic age alone is insufficient to decide on the management plan. Comprehensive geriatric assessment with evaluation on patients’ functional status, mental condition, estimated life expectancy, comorbidities, risks and benefits of the treatment, patients’ preference, and family support is essential. In addition, little data from randomized controlled trials are available to guide treatment decisions in elderly patients with NPC. In deciding which treatment strategy would be suitable for an individual elderly patient, we reviewed the literature and reviewed the analysis of primary studies, reviews, and guidelines on management of NPC. This review also summarises the current evidence for NPC management in elderly adults from early to late stage of disease.